Pengukuran Karakteristik Dielektrik Minyak Goreng Berdasarkan Lama Pemanasan Menggunakan Rangkaian Sederhana Multivibrator IC 555 - Misto, Misto; Y.A, Muhtarom; Supriyadi, Supriyadi (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2019)
An electronic system for cooking oil dielectric  constant measurement have been done. The system was employed an capacitive sensor, IC Timer 555, oscilloscope, and power supply. The cooking oil is placed in a capacitive sensor as part of unstable multivibrator IC 555 circuit. The samples(labeled and non labeled) temperature was condisioned on room temperature and at 100 ⁰C with the heated time duration of 1 hours, 2 hours, and 3 hours treatment.   The result of  the measurement shows that all sample with time duration 1 hours and 2 hours increases but with time duration 3 hours turn down.Data SDYhttps://materassomemory.org/https://visualresearchnetwork.org/https://brazoriafumc.org/https://atmamayor.com/https://viralblasts.com/Bloom ScapeRokokbetRokokbetScatter HitamRokokbethttps://press.umam.edu.my/Rokokbethttps://theusajournals.com/RokokbetShiowlaRokokbetRokokbetRokokbetRokokbetRokokbetShiowla